Portable and platform‐independent MR pulse sequence programs - Cordes, Cristoffer; Konstandin, Simon; Porter, David; Günther, Matthias (Magnetic resonance in medicine, 2020)
Purpose To introduce a new sequence description format for vendor‐independent MR sequences that include all calculation logic portably. To introduce a new MRI sequence development approach which utilizes flexibly reusable modules. Methods The proposed sequence description contains a sequence module hierarchy for loop and group logic, which is enhanced by a novel strategy for performing efficient parameter and pulse shape calculation. These calculations are powered by a flow graph structure. By using the flow graph, all calculations are performed with no redundancy and without requiring preprocessing. The generation of this interpretable structure is a separate step that combines MRI techniques while actively considering their context. The driver interface is slim and highly flexible through scripting support. The sequences do not require any vendor‐specific compiling or processing step. A vendor‐independent frontend for sequence configuration can be used. Tests that ensure physical feasibility of the sequence are integrated into the calculation logic. Results The framework was used to define a set of standard sequences. Resulting images were compared to respective images acquired with sequences provided by the device manufacturer. Images were acquired using a standard commercial MRI system. Conclusions The approach produces configurable, vendor‐independent sequences, whose configurability enables rapid prototyping. The transparent data structure simplifies the process of sharing reproducible sequences, modules, and techniques.